Extraskeletal Ewing sarcoma: report of a rare and exuberant case simulating lipoma - Alfredo, Melissa de Almeida Corrêa [UNESP]; Lacerda, Priscila Neri [UNESP]; Abreu, Ana Flávia Teixeira [UNESP]; Carneiro, Alexandre Morais [UNESP]; Campos, Eloisa Bueno Pires [UNESP]; Miot, Helio Amante [UNESP] (GN1 Sistemas e Publicacoes, 2023)
Extraskeletal Ewing sarcoma (EES) is a rare tumor that affects men between 10-20 years old and represents 25% of Ewing sarcomas. We report a case due to the previous diagnosis of a fast-growing lipoma to highlight the importance of histopathological diagnosis. A 14-year-old boy presented 10x10 cm tumor in the right shoulder for a year with ultrasonography suggesting lipoma. The lesion was excised and EES was confirmed by immunohistochemical analysis. EES diagnosis in young people is challenging compared to subcutaneous tumors, and histopathology is essential. The rapid progression of the tumor and high metastatic rates highlight the significance of early treatment.
Sarcoma de Ewing extraesquelético: relato de um caso raro e exuberante simulando lipoma
Keywords: Ewing; Neuroectodermal tumors; Sarcoma